Model Penentuan Urgensi Perbaikan Tower Menggunakan Metode MOORA - Abdurrasyid Abdurrasyid; Teguh Aryo Nugroho; Didik Fauzi Dakhlan; Arry Akhmad Arman; Dimitri Mahayana (Jurnal Informatika, 2022)
Quality control can suppress or reduce the volume of errors and repairs in the future where it can also minimize costs incurred by the company if later there is damage. These activities must be carried out carefully and effectively so that the results obtained are in accordance with the initial objectives. In fact, the implementation of equipment quality control activities in the field at PT. Indonesia Comnets Plus SBU Regional Sumbagsel is still done manually so it is not practical and takes a lot of time. This research is a design science research (DSR) by making a decision support system to help determine the quality of equipment in the field and determine the level of urgency for repairs to the tower that suffered the most damage using the Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) Method. The accuracy results obtained in the implementation of this method are 100%